Pengaruh Profitabilitas, Risiko Bisnis, Kepemilikan Manajerial, Dan Pajak Terhadap Struktur Modal - Melisa Rahmadianti; Yuliandi Yuliandi (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
The purpose of this study was to determine the effect of profitability, business risk, managerial ownership, and tax on the capital structure of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. Capital structure is proxied by debt to equity ratio. The population in this study are all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2014-2017. Sample selection through purposive sampling method. There are 12 companies that meet the criteria as research samples so that the observation data is around 48. This study supports literature studies by processing secondary data obtained from annual reports. The analytical method used is multiple linear regression analysis through the program SPSS version 23. The results of this study indicate that profitability, business risk, managerial ownership, and tax simultaneously affect the capital structure with a significance level of 0,000. Partially profitability, business risk, and tax affect the capital structure with a significance level of 0,000. Managerial ownership partially does not affect the capital structure with a significance level of 0,058. Keywords : Profitability, business risk, managerial ownership, tax, capital structure.